Binomial

Algebra Level 2
  1. The sum of the numerical coefficients in the expansion of the binomial ( a + b ) 6 (a+b)^6 is


The answer is 64.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

10 solutions

Nikko Quirap
Apr 12, 2014

Let S be the Sum of Coefficients

S=(coef. of A + coef. B)^n

S=(1+1)^6

S= 2^6

S=64

nCr nC0 + nC1+ nC2 +......+ nCn = 2^n

Ameya Salankar
Apr 5, 2014

@Ashtik Mahapatra Why did you write (a+b^6)? It looks like a + b 6 a+b^6 . I was absolutely sure that it is ( a + b ) 6 (a+b)^6 & I didn't go wrong. Edit the question immediately .

Well, we solve it using Pascal's Triangle . Make the triangle until its first six levels & add the sixth row which is

1 + 6 + 15 + 20 + 15 + 6 + 1 = 1+6+15+20+15+6+1 = 64 \boxed{64} .

That's unnecessary.It is known that the sum of the binomial coefficients

( n 0 ) + ( n 1 ) + . . . + ( n n ) = 2 n \displaystyle\binom{n}{0}+\binom{n}{1}+...+\binom{n}{n}=2^n .

In this case n=6, so our answer is 2 6 = 64 2^6=64

Bogdan Simeonov - 7 years, 2 months ago

Log in to reply

@Bogdan Simeonov Pascal's Triangle is based on this very principle!

Ameya Salankar - 7 years, 2 months ago

Log in to reply

Yes, I know that, but why did you sum them?You could have just said 2 6 2^6 and that's it.

Bogdan Simeonov - 7 years, 2 months ago

@Ameya Salankar I am very sorry for this mistake. In fact I had not checked the question. I have edited it. Thanks for letting me know

Ashtik Mahapatra - 7 years, 2 months ago

I am happy to see that you didn't go wrong for my mistake, otherwise I would have felt too guilty. Actually for these small mistakes in the questions we get it wrong and our ratings drop.

Ashtik Mahapatra - 7 years, 2 months ago

Log in to reply

@Ashtik Mahapatra Notice that ratings drop on problems which are rated by moderators . Your problem was not rated by moderators so the ratings wouldn't have dropped. Anyway, you could have used L A T E X LATEX though.

Ameya Salankar - 7 years, 2 months ago

Log in to reply

Sorry but I don't., know how to use LATEX

Ashtik Mahapatra - 7 years, 2 months ago

Log in to reply

@Ashtik Mahapatra @Ashtik Mahapatra You can make this site a bookmark. Without L A T E X LATEX , you miss out on half the fun on Brilliant!

Ameya Salankar - 7 years, 2 months ago
Syed Hamza Khalid
Oct 27, 2017

Use the pascal's triangle: { Sixth row }

Sangeetha Sangu
Apr 28, 2015

Solve it using pascals triangle 1 1 1 -> (a+b)¹ 1 2 1 -> (a+b)² 1 3 3 1..so on........ For (a+b)^6 ... The nos are
1 6 15 20 15 6 1... Sum of which is 64

Preyans Raval
May 21, 2014

there is a short-cut method for finding the sum of co-efficients in binomial... we can find it by putting all variables=1... so(a+b)^6 = (2)^6 = 64

Pavel Hossain
Apr 20, 2014

by the law of pascel 1 1 2 1 1 3 3 1 1 4 6 4 1 1 5 10 10 5 1 1 6 15 20 15 6 1 so (1+6+15+20+15+6+1)=64

Shreyansh Vats
Apr 15, 2014

Use of the Pascal's Triangle helps to cap off.

Does "cap off" mean the same as "hats off"?

Satvik Golechha - 7 years, 1 month ago
Vighnesh Raut
Apr 11, 2014

Draw a pascal's Triangle and add all the numbers of line 6...Simplest way to do it..

Datu Oen
Apr 11, 2014

Note that in expanding ( a + b ) 6 (a + b)^6 , we have:

( a + b ) 6 = a 6 + 6 C 1 a 5 b + 6 C 2 a 4 b 2 + 6 C 3 a 3 b 3 + 6 C 4 a 2 b 4 + 6 C 5 a b 5 + b 6 (a + b)^6 = a^6 + _6C_1 a^5\cdot b + _6C_2 a^4\cdot b^2 + _6C_3 a^3\cdot b^3 + _6C_4 a^2\cdot b^4 + _6C_5 a\cdot b^5 + b^6 .

And if we let a = b = 1 a = b = 1 we are left with the coefficient on the right side of the equation. That is we have:

1 6 + 6 C 1 1 5 1 + 6 C 2 1 4 1 2 + 6 C 3 1 3 1 3 + 6 C 4 1 2 1 4 + 6 C 5 1 1 5 + 1 6 1^6 + _6C_1 1^5\cdot 1 + _6C_2 1^4\cdot 1^2 + _6C_3 1^3\cdot 1^3 + _6C_4 1^2\cdot 1^4 + _6C_5 1\cdot 1^5 + 1^6

= 1 + 6 C 1 + 6 C 2 + 6 C 3 + 6 C 4 + 6 C 5 + 1 =1 + _6C_1 + _6C_2 + _6C_3 + _6C_4 + _6C_5 + 1

= 1 + 6 + 15 + 20 + 15 + 6 + 1 = 64 = 1 + 6 +15 + 20 + 15 + 6 + 1 = 64

Since we let a = b = 1 a = b = 1 , the left side of the expansion ( a + b ) 6 (a + b)^6 becomes ( 1 + 1 ) 6 = 2 6 = 64 (1 + 1)^6 = 2^6 = 64

We can actually extend this.

For example, we wish to determine the sum of the coefficient of the binomial expansion ( a + b ) n (a + b)^n , where n N n \in N , then the coefficient can be computed by letting a = b = 1 a = b = 1 . That is, the sum of the numerical coefficient will be 2 n 2^n

We can still extend this. What if we have numerical coefficient in the binomial.

For example, what is the sum of the numerical coefficient of ( 2 a + 3 b ) 2 ? (2a + 3b)^2?

Since ( 2 a + 3 b ) 2 = ( 2 a ) 2 + 2 ( 2 a ) ( 3 b ) + ( 3 b ) 2 = 4 a 2 + 12 a b + 9 b 2 (2a + 3b)^2 = (2a)^2 + 2(2a)(3b) + (3b)^2 = 4a^2 + 12ab + 9b^2 . We can easily see that the sum of the coefficient is 4 + 12 + 9 = 25 4 + 12 + 9 = 25 .

However, if we let a = b = 1 a = b = 1 we get ( 2 + 3 ) 2 = 5 2 = 25 (2 + 3)^2 = 5^2 = 25 which is our answer.

Now let us try finding the sum of the coefficient of ( 2 a 3 b ) 4 (2a -3b)^4 . You can check that the answer is 1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...